Assessment of wheel propeller contact pressure upon soil with use of tire universal performance - Z. A. Godzhaev; A. Yu. Izmaylov; V. G. Shevtsov; A. V. Lavrov; A. V. Rusanov (Сельскохозяйственные машины и технологии)
A maximum contact pressure is a key parameter characterizing a level of ecological impact of tractor propellers on the soil. The maximum pressure upon the soil varies with internal pressure in tires and vertical load of a wheel. An universal tire performance can be used at an assessment of change of contact pressure of a wheel propeller upon the soil. The authors offered a technique of definition and regulation of the maximum contact pressure of the wheel propeller upon the basic basis. This technique allows to set parameters for monitoring systems and regulation of the maximum pressure upon the soil by measurement of a tire deflection and change of pressure in tires. At statistical tests for determination of the maximum contact pressure it is necessary to consider the universal performance of the tire nomographically. This nomogram allows to consider visually influence of loading and internal pressure in the tire on a size of the maximum contact pressure. An internal pressure decrease in the tire makes it possible to reduce the maximum pressure upon the soil at constant loading. The authors investigated universal performances of the tires in the range of change of internal air pressure from 160 to 90 kPas. Change of internal pressure from 150 to 100 kPas reduce for the tire 15,5R38 the maximum contact pressure upon 13 kPas (9,6 percent): from 135 to 122 kPas. That corresponds to the admissible level of pressure upon the soil at its humidity in a layer of 0-30 cm: 0,5-0,6 minimum moisture-holding capacity during the spring period and 0,6-0,7 minimum moisture-holding capacity during the autumn period. In case of use of the tire 16,9R38 the maximum pressure upon the soil decreases from 84 to 75 kPas, that is by 10,4 percent.